Seismic response of horizontally curved bridges in combination with skewed abutments. (February 2022) - Gupta, Tanmay; Sandhu, Dikshit
Abstract: A bridge having in-plan curvature in combination with the skewed abutments is termed as skew-curved bridge. Present study explores upon the seismic response of a three-span continuous RC skew-curved concrete box-girder bridges under free and forced vibrations for which 3-D models of the bridge with varying configurations are generated in the CSiBridge. The curvature angle for the parametric study has been varied as 0°, 30°, 60° and 90° in combination with skew angles of 0°, 15°, 30°, 45° and 60°. Modal analysis and response spectrum analysis for all the bridge models has been performed. Modal response of the various bridge configurations has been presented in graphical form in order to have knowledge of the mode shapes, time periods and fundamental frequencies of the bridges. Based on guidelines of AASHTO 2007 response spectrum analysis has been performed considering 0.3 g acceleration in longitudinal and transverse direction and an acceleration of 0.2 g in vertical direction. In-plane bending moments, longitudinal torsion and out-of-plane bending moments are monitored for all skew curved bridges under longitudinal, transverse and vertical excitations and it is observed that especially in-plane moments in longitudinal and transverse direction are significantly affected by inclusion of skewness and curvature in bridges.